Green mergers and acquisitions as a driver for better corporate sustainability practices : Special role of environmental, social, and governance frameworks with financial performance in Europe - Nikkilä, Hanna (My University, 2025)
Sustaining competitive advantage requires firms to adapt to evolving legal standards and place greater emphasis on environmental, social, and governance (ESG) practices. ESG is nowadays a critical and common component in companies’ strategies. Europe seeks to become the world’s first carbon-neutral continent by 2050 under the European Union (EU) Green Deal, necessitating companies to adopt and further develop their ESG frameworks. Companies can embed ESG into their strategy differently and thus comply with the EU Corporate Sustainability Reporting Directive (CSRD). When lacking resources and knowledge on ESG practices and to achieve a competitive advantage, companies can pursue mergers and acquisitions (M&A). Conventionally, M&A have been compelling to expand market opportunities, financial synergies, and cost efficiency. M&A is a high-risk strategic decision that enables companies to gain better ESG performance. This thesis examines how ESG performance changes without compromising corporate financial performance (CFP) in a green M&A in the EU. Especially when acquiring a higher ESG target, the acquirer benefits from the ESG practices in the target company, which is seen in the ESG score increase. Scoring for ESG practices is used in investment activities and reflects non-financial activities. The ESG score is given by rating agencies based on available non-financial reports from the company. The scoring is divided into an overall score and three pillars: environmental responsibility, social responsibility, and good governance. The overall score is a combination of these three separate pillars. The scores are delivered as a numeric (for example, 0-100) or letter-based (for instance, AAA-D), depending on the rating agency. They are widely used variables to study CFP or M&A success through a sustainability lens. The commitment to ESG aligns closely with adherence to the triple bottom line (TBL) framework encompassing people, planet, and profit (3P). The TBL and ESG stem from corporate social responsibility (CSR), and the ESG score can be used to measure CSR activities. Advancing ESG practices holds little strategic relevance unless aligned with favorable financial outcomes. This thesis gives a valuable insight into the interrelation between ESG and CFP, along with M&A as a strategic tool to obtain better ESG practices. Governance and social pillars indicate better integration between the companies involved in M&A, whereas the environmental pillar has the most influence on determining the CFP. This thesis recognizes shareholder expectations and argues that, beyond maximizing shareholder value, ESG engagement is financially sound and delivers tangible and intangible value that resonates with all stakeholders. Combining the implication of finding a competitive advantage, the M&A seems to be a feasible strategic decision to acquire better ESG practices and enable European companies to be part of the EU´s green deal initiative. Green M&A deals, in particular, enable companies to develop sustainable environmental practices while aligning with financial objectives. The findings highlight the central role of corporate responsibility principles in strategic management and their significant impact on the planning and implementation of corporate acquisitions in today's business context.

Kilpailuedun ylläpitäminen edellyttää yrityksiltä sopeutumista muuttuviin lakisääteisiin standardeihin sekä yritysvastuuseen, mikä pitää sisällään ympäristövastuun, sosiaalisen vastuun ja hyvän hallintotavan. Yritysvastuu on nykyään kriittinen ja yleinen osa yritysten strategiaa. Ilmastonmuutoksen torjumiseksi ja Euroopan unionin (EU) vihreän kehityksen ohjelman tavoitteiden saavuttamiseksi, yritykset ovat parantaneet ja parantavat edelleen yritysvastuukäytänteitään. Vihreän kehityksen ohjelman tavoitteena on, että Euroopasta tulee ensimmäinen hiilivapaa maanosa vuoteen 2050 mennessä. Yritykset voivat sisällyttää yritysvastuukäytänteitään strategiaansa eri tavoin ja näin noudattaa EU:n kestävyysraportointidirektiiviä. Yritysvastuukäytäntöihin liittyvien resurssien ja tietojen puuttuessa, yritys voi saavuttaa kilpailuetua toteuttamalla yritysfuusion tai -kaupan ja hankkia ko. resursseja ja tietoa. Perinteisesti yritysfuusiot ja -kaupat ovat olleet houkuttelevia markkinamahdollisuuksien, taloudellisten synergioiden ja kustannustehokkuuden aikaansaamiseksi, vaikka ne ovatkin korkean riskin strateginen päätös, jonka avulla yritykset voivat parantaa yritysvastuutaan. Tämä opinnäytetyö tarkastelee, miten ESG-suorituskyky muuttuu vaarantamatta yritysten taloudellista suorituskykyä vihreän yrityskaupan yhteydessä EU:ssa. Erityisesti ostettavan yrityksen paremmat yritysvastuukäytänteet hyödyttävät ostajaa saavuttamaan paremmat yritysvastuu käytänteet, mikä näkyy ympäristövastuun, sosiaalisen vastuun sekä hallinnointitapojen pistemäärän nousuna. Pistemäärät annetaan ulkopuolisten toimijoiden arvioinnin perusteella, pohjautuen yrityksistä saatavilla oleviin ei-taloudellisiin raportteihin. Pisteytys on jaettu kokonaispistemäärään sekä kolmeen pilariin: ympäristövastuuseen, sosiaaliseen vastuuseen ja hyvään hallintotapaan. Kokonaispistemäärä on näiden kolmen erillisen pilarin yhdistelmä. Riippuen toimijasta, pisteet annetaan numeerisina tai kirjaimin, ja niitä käytetään laajalti yritysten taloudellisen suorituskyvyn ja yritysfuusioiden ja -kauppojen onnistumisen osoittamiseksi kestävän kehityksen näkökulmasta. Sitoutuminen ympäristöön, sosiaaliseen vastuuseen ja hyvään hallintotapaan on linjassa kolmoistilinpäätöksen noudattamisen kanssa, mikä kattaa ihmiset, planeetan ja voiton. Kolmoistilinpäätös sekä yritysvastuu juontavat juurensa yritysten yhteiskuntavastuusta, ja edellä kuvattuja pistemääriä voidaan käyttää yritysvastuutoiminnan mittaamiseen ja apuna sijoitustoiminnassa. Sitoutumisella yritysvastuuseen on vain vähän strategista merkitystä, ellei se ole linjassa yrityksen taloudellisen tuloksen kanssa. Tämä tutkielma antaa arvokkaan käsityksen, miten yrityksen sitoutumista ympäristöön, sosiaaliseen vastuuseen ja hyvään hallintotapaan voidaan hyödyntää yritysfuusioissa ja -kaupoissa strategisena työkaluna paremman yritysvastuukäytäntöjen saavuttamiseksi. Hyvän hallintotavan ja sosiaalisen vastuun pilarit parantavat integraatiota yrityskaupoissa, kun taas ympäristöpilarilla on suurin vaikutus taloudelliseen suorituskykyyn. Tutkielma tunnistaa osakkeenomistajien odotukset ja väittää, että osakkeenomistajien arvon maksimoimisen lisäksi yritysvastuu on taloudellisesti järkevää ja tuottaa sekä konkreettista että aineetonta arvoa, joka resonoi kaikkien sidosryhmien kanssa. Yhdistämällä kilpailuedun saavuttamisen merkityksen, yrityskaupat vaikuttavat toteuttamiskelpoiselta strategiselta päätökseltä parempien yritysvastuukäytäntöjen omaksumiseksi ja mahdollistavan eurooppalaisten yritysten osallistumisen EU:n vihreän kehityksen ohjelmaan. Erityisesti vihreät yrityskaupat mahdollistavat kestävien ympäristökäytäntöjen omaksumisen samalla, kun ne ovat linjassa taloudellisten tavoitteidensa kanssa. Tutkielma tuo esiin yritysvastuuperiaatteiden keskeisen aseman strategisessa johtamisessa sekä niiden merkittävän vaikutuksen yrityskauppojen suunnitteluun ja toteutukseen nykypäivän liiketoimintakontekstissa.
Keywords: Environment, social and governance responsibility, corporate financial performance, environment, social and governance score, mergers and acquisitions, corporate social responsibility, ympäristövastuu, sosiaalinen vastuu, hyvät hallintotavat, yritysvastuu, yrityksen taloudellinen suorituskyky, fuusiot ja yrityskaupat, yritysvastuu